Asesmen Formatif: Analisis Psikometrik Instrumen Menggunakan Model Rasch pada Materi Teorema Pythagoras - Irmawaty Natsir; Anis Munfarikhatin; Khumairoh Dwi Nur'aini; Nurhayati; Nurmayaningsih; Wiwik Andriani (Media Pendidikan Matematika, 2026)
This study uses a quantitative approach that aims to analyze the psychometric characteristics of formative assessment instruments using the Rasch Model. The research sample consisted of 20 students. The instrument used was a multiple-choice test consisting of 20 questions on the Pythagorean Theorem. Data were analyzed using Winsteps to identify instrument reliability, item difficulty level, item fit, person measure, and student response patterns. The results showed that the instrument had a fairly good reliability with a Cronbach Alpha value of 0.70, person reliability of 0.67, and item reliability of 0.77. Analysis of item difficulty levels showed that there were 2 items in the very easy category, 7 items in the easy category, 8 items in the difficult category, and 3 items in the very difficult category. The results of the item fit analysis showed that most of the items were in accordance with the Rasch Model, although there is one item that needs to be revised because it does not meet the model suitability criteria. Analysis of student abilities showed that most students were in the medium to high ability category. In addition, the results of the Wright Map and Scalogram showed that the instrument had a fairly good ability to differentiate student abilities. Thus, the developed formative assessment instrument can be used to measure students' abilities in the Pythagorean Theorem material.